UMPSA strengthens sustainable agriculture through Ketum Ayam Project - Nur Ain Zakiah, Mohd Yusof; Rozana, Sahadan; Jamilah Bebe, Mohamad (UMPSA, 2025)
SETIU, 18 January 2025 – A total of 60 residents attended the launching ceremony of the Ketum Ayam (Trichantera gigantea) Project, including 20 farmers who have registered to participate in the programme offered by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) in Kampung Ulu Kekabu, Setiu.